2023
DOI: 10.1099/mgen.0.001028
|View full text |Cite
|
Sign up to set email alerts
|

A panoramic view of the genomic landscape of the genus Streptomyces

Marios Nikolaidis,
Andrew Hesketh,
Nikoletta Frangou
et al.

Abstract: We delineate the evolutionary plasticity of the ecologically and biotechnologically important genus Streptomyces , by analysing the genomes of 213 species. Streptomycetes genomes demonstrate high levels of internal homology, whereas the genome of their last common ancestor was already complex. Importantly, we identify the species-specific fingerprint proteins that characterize each species. Even among closely related species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 94 publications
(158 reference statements)
4
7
0
Order By: Relevance
“…The number of BGCs per genome in our dataset ranged from 19 to 65 (median=42.5) (Fig. 3a), which is consistent with those reported in other studies of Streptomyces [45][46][47]. We detected a significant positive correlation albeit small between the genome size and the number of BGCs per genome (R 2 =0.13, p-value=3.1e-05; Fig.…”
Section: Bgcs Are Diverse and Abundant But Not Structured By The Sour...supporting
confidence: 91%
“…The number of BGCs per genome in our dataset ranged from 19 to 65 (median=42.5) (Fig. 3a), which is consistent with those reported in other studies of Streptomyces [45][46][47]. We detected a significant positive correlation albeit small between the genome size and the number of BGCs per genome (R 2 =0.13, p-value=3.1e-05; Fig.…”
Section: Bgcs Are Diverse and Abundant But Not Structured By The Sour...supporting
confidence: 91%
“…Each genome presents 16 to 53 BGCs, consistent with the most recent metagenomic studies [38]. The strains situated at the extremities of the range are Streptomyces sp.…”
Section: Distribution and Diversity Of Biosynthetic Gene Clusters (Bg...supporting
confidence: 84%
“…HSG2 to 12.47 Mb for Streptomyces rapamycinicus NRRL 5491, with an average of 8.3 Mb. Despite the increased genomic information available for this genus, the genome size values are very close to those reported in previous metagenomic analyses[21,38,39].…”
supporting
confidence: 80%
“…While the importance of optimized growth medium for metabolite production and life cycle progression is widely recognized, few have examined nutrient poor conditions. The abundance of gene regulatory proteins, two-component systems, transporters, and substrate-binding proteins identified in the S. coelicolor genome suggests a significant capacity for adaptation and the utilization of varied nutrient sources (Bentley et al, 2002; Nikolaidis et al, 2023). A recent study on rich media showed that S. coelicolor metabolite production was enhanced because of genomic heterogeneity (Z.…”
Section: Introductionmentioning
confidence: 99%